Effect of ketotifen fumarate on experimental autoimmune orchitis and torsion of the spermatic cord - Moreno, Diego Javier (2020)
The aim of this work was to study effects of ketotifen fumarate (KF) on prevention of tissue damage in testes of rats with experimental autoimmune orchitis (EAO) and on the contralateral testis in a model of prolonged testicular cord torsion (TCT). Rats with EAO or TCT were injected intraperitoneally once daily with KF or saline solution (vehicle group). Incidence and severity of testicular damage were evaluated by histopathology using an EAO score or a Johnsen score. Mast cells (MC) were identified by histochemistry and quantified. In EAO model, KF significantly reduced severity of histopathological testicular damage compared to rats in the vehicle group. KF also reduced the number of testicular MC compared to vehicle group. Similarly, in TCT model, multifocal damage of the contralateral testis was observed 30 days after testicular torsion characterized by sloughing of the germinal epithelium, seminiferous tubule atrophy, and interstitial edema. Focal signs of inflammation and fibrosis of seminiferous tubular walls were also observed. In contrast, sections of contralateral testis of rats injected with KF and killed 30 days after surgery showed normal histological features. A significant decrease in the number of MC was observed in rats treated with KF compared to untreated animals. In conclusion, we demonstrated that treatment with KF reduced testicular inflammatory process and MC infiltrates in both EAO and TCT models. The results suggest a promising treatment for infertile male patients with testicular pathologies associated with inflammation and germ cell loss.